OPTIMALISASI PEMESANAN BAHAN BAKU DI PT XYZ UNTUK MEREDUKSI BIAYA PERSEDIAAN DENGAN METODE PROGRAM DINAMIS - Soenandi, Iwan Aang (Teknik dan Ilmu Komputer, 2012)
The raw material is something important for the company especially for the production process. If the company have too much raw materials, it will result in high cost of purchase, storage, and maintenance at the warehouse. Meanwhile, if a little bit of raw materials owned, it will cause a great loss to the company because they could not fulfill the sales demand. Therefore, to maintain the production process running smoothly required a good planning and control of raw materials.Â Keywords:Â  Production Process, Optimization, Dynamic Programming